The UMP Foundations Asean Exploration Journey honours the Muslim community in Cambodia - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2023)
PHNOM PENH, 17 November 2023 - The Universiti Malaysia Pahang Foundation successfully organized the Kembara Eksplorasi Asean@Phnom Penh,Cambodia from 11 to 17 November.